Behavioural modelling and power quality simulation of a HVDC electric power system for MEA. Issue 13 (12th April 2018) - Yue, Wang; Yannian, Hui; Yuanli, Kang
Abstract : High‐voltage direct current (HVDC) electric power system (EPS) is a promising architecture for more electric aircraft (MEA). With more electric power used, a higher voltage is necessary to make aircrafts more efficient and less weighted. However, there are no standards can be followed to evaluate the power quality of HVDC EPS, especially for 540 VDC system. In this study, a potential HVDC EPS is proposed and power quality is studied by simulation. Behavioural models of the system are established in detail from source to load. Three kinds of typical loads of MEA are defined and their impacts on power quality are analysed including resistances, power electronic converters, and motors. Some suggestions are provided for design and integration of the EPS for MEA.